2021
DOI: 10.1002/dac.4916
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of different LED lamp configurations in indoor VLC system

Abstract: Summary In this article, an indoor environment of 5 × 5 × 3 m3 dimensions is considered and a total of nine LED lamps are installed at the ceiling in a symmetrical pattern. The inter‐spatial separation between LED lamps is varied to achieve the dual purpose of lighting and communication services. The multipath channel impulse response for distinct receiver locations is also calculated under line‐of‐sight (LOS) and non‐line‐of‐sight (NLOS) channel conditions. Several performance parameters, that is, illuminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Related studies have shown that the improvement of communication channels helps to enhance the communication performance of the system. Both LOS channels and non-LOS (NLOS) channels are analyzed in the literature [ 33 , 34 , 35 ]. Mohanna et al [ 33 ] analyzed the effect of reflected light from walls on the receiver side by simulating a LOS channel and an NLOS channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies have shown that the improvement of communication channels helps to enhance the communication performance of the system. Both LOS channels and non-LOS (NLOS) channels are analyzed in the literature [ 33 , 34 , 35 ]. Mohanna et al [ 33 ] analyzed the effect of reflected light from walls on the receiver side by simulating a LOS channel and an NLOS channel.…”
Section: Introductionmentioning
confidence: 99%
“…Mohanna et al [ 33 ] analyzed the effect of reflected light from walls on the receiver side by simulating a LOS channel and an NLOS channel. By arranging multiple LEDs in both LOS and NLOS channels, Priyanka et al [ 34 ] improved the uniformity of light illumination within the communication channel and mitigated the effect of inter-symbol interference. Long [ 35 ] researched the performance evaluation of a VLC system with various FOVs, elevation and azimuth receivers by simulating LOS and NLOS models.…”
Section: Introductionmentioning
confidence: 99%